Daljinski nadzor potisne peči - Jaklič, Anton (Kovine zlitine tehnologije, 1999)
A remote monitoring of pusher type furnace was developed. Communication is based on industrial ethernet network system under TCP-IP communication protocol. Simulation experiment works under UNIX-Linux environment and allows also calculations of non-measurable values in real-time. The emphasis in the paper is on: the flow chart of simulation experiments, its adoption on real object and the using of files for real-time graphical presentation.
Keywords: daljinski nadzor; simulacije; potisna peč